Non pharmacologic pain management on oncologic patients: systematic review - Marina Araújo Vahia Abreu; Paula Elaine Diniz Reis; Isabelle Pimentel Gomes; Priscila Roberta Silva Rocha (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Non pharmacologic therapies, also classified as complementary or alternative therapy has been used to control pain in many patients. In order to know which non pharmacologic interventions are being used for pain relief in patients with cancer, it was conducting a systematic review of the literature. We selected five articles that consider educational strategies for patients, families and professionals as well as guided imagery as possible non pharmacologic interventions for the management of pain in cancer patients. It is crucial that the multidisciplinary team in oncology, and keep updated their knowledge on prevention, treatment, control and relief of pain, also start the challenge of improving and diversifying practices for management of pain in an individual.